“Nothing is easy to understand”: reflections on the suicide act in adolescence (Research, Society and Development, 2021)
Suicide is a public health problem that affects communities, cities and countries, being the second leading cause of death among young people aged 15 to 29 years. In this context, this work aims to investigate the possible contributions of psychoanalysis in the context of acting in situations of suicide in adolescents, pointing out the possibility of interlocution and reflections between psychoanalysis and health promotion based on an analysis of excerpts from the music Pais e Filhos - (Urban Legion, 1989). This is an exploratory type research, with qualitative method, empirical documentary, with survey to identify potential studies in databases, with categorization of themes, and search for psychoanalytic theoretical correlation. The results and discussion point to the possibilities of contributions from Psychoanalysis to situations of suicide and self-mutilation in adolescence, interlocutions between psychoanalysis and public health and reflections on welcoming and care in psychological practices. The final considerations of the study show the importance of the Psychology professional in the field of public health, unveiling issues related to the practice of psychoanalysis in the thematic suicidal act in adolescence.